The Study of Safety Standard and Education Value on Children Playground Age 3-5 year in Shopping Center (Descriptive Study in 'Wonderland-Adventure' Shopping Center ADA Siliwangi Semarang) - Wulantika, Surya; Diana, Diana (Jurusan PGPAUD FIP UNNES, 2017)
In globalization era the entertainment industry for family is growing up as fast as the changing of urban people life style. Playing is one of children needs that must be fullfilled to complete their growing mass. Shopping center which equipped with children playground is an alternative facility to serve entertainment and recreation that needed by people. The safety standard and education value on playground in shopping center must be noticed. Purpose of this study is know the safety standard and education value on â€œWonderland Adventureâ€ playground in ADA Swalayan shopping center in Siliwangi Semarang. This study uses qualitative research with descriptive study. Subject of this study is supervisor as main informant, leader as supporting informant, and visitor as triangulation informant. Method and technique of data collection of this study are interview, observation, and document analysis. Data analysis of this study is Interactive Miles & Huberman data analysis. Based on result of this study can be concluded if the safety standard on â€œWonderland Adventureâ€ playground in ADA Swalayan Siliwangi Semarang shopping center is good enough. The administrator always checks the games routinely, at morning, noon, and afternoon. The administrator also pours antiseptic solution when cleaning playground so that always kept its clean. Whereas for education value on â€œWonderland Adventureâ€ playground must be increased. That is according to the types of games available which aimed to develop childrensâ€™ crude motoric capability, and for games which develops cognitive capability and accuracy are not available yet.